2018
DOI: 10.1155/2018/6256802
|View full text |Cite
|
Sign up to set email alerts
|

Dietary DHA/EPA Ratio Changes Fatty Acid Composition and Attenuates Diet‐Induced Accumulation of Lipid in the Liver of ApoE−/− Mice

Abstract: Diets containing various docosahexaenoic acid (DHA)/eicosapentaenoic acid (EPA) ratios protect against liver damage in mice fed with a high-fat diet (HFD). However, it is unclear whether these beneficial roles of DHA and EPA are associated with alterations of fatty acid (FA) composition in the liver. This study evaluated the positive impacts of n-6/n-3 polyunsaturated fatty acids (PUFAs) containing different DHA/EPA ratios on HFD-induced liver disease and alterations of the hepatic FA composition. ApoE−/− mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…Thus, increasing AMPK activities has been considered as a therapeutic approach to improve NAFLD [124]. Although several studies conducted in younger mice models of NAFLD have illustrated that short-or medium-term n-3 PUFA supplementation [27,82,94,125,126], and exercise interventions [37,39,106,111,127,128] can increase AMPK activation, to our knowledge our study is the first addressing the combined effects of long-term n-3 PUFA supplementation and exercise training on AMPK activation in obese aged mice.…”
Section: Discussionmentioning
confidence: 97%
“…Thus, increasing AMPK activities has been considered as a therapeutic approach to improve NAFLD [124]. Although several studies conducted in younger mice models of NAFLD have illustrated that short-or medium-term n-3 PUFA supplementation [27,82,94,125,126], and exercise interventions [37,39,106,111,127,128] can increase AMPK activation, to our knowledge our study is the first addressing the combined effects of long-term n-3 PUFA supplementation and exercise training on AMPK activation in obese aged mice.…”
Section: Discussionmentioning
confidence: 97%
“…However, the fish oils used in these studies were commercially available fish oil with a higher EPA content (Molinar-Toribio et al, 2015;Parker et al, 2019). Additional evidence has indicated the role of the ratios of DHA and EPA in the prevention and treatment of chronic disease in rat models (Liu et al, 2018;Molinar-Toribio et al, 2015). Furthermore, a study (Cottin et al, 2011) explored the known differential effects of EPA and DHA in human subjects and concluded that there is an F I G U R E 5 Changes in the gut microbiota related to HDTO and TO supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…The present study used diets with similar omega-6 FA content and higher preformed DHA, but not EPA in DHA diet, in order to decrease confounding by individual and rate-limiting differences in long-chain polyunsaturated fatty acid metabolism [41]. Furthermore, the herein used concentration has been shown to increase DHA serum and tissue concentrations [31,42], which was beneficial in pulmonary and neurological diseases in rodents [32,33]. Male mice were chosen to eliminate the complex cardioprotective effects that have been reported for all estrogen receptor subtypes against I/R injury, and a purified diet was chosen as the basis for both diets to avoid variability in standard chows [43].…”
Section: Discussionmentioning
confidence: 99%